Effect Of Coating Thickness On The Microstructure And Mechanical Properties Of AL-SI (LM6) Alloy Lost Wax Casting / Mohamad Ridzuan Mohamad Kamal...[et al.] - Mohamad Kamal, Mohamad Ridzuan; Abdul Rahman, Abdul Raheem; Wakhi Anuar, Nur Farah Bazilah; Salleh, Mohd Shukor (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In the work, the effect of slurry and stucco coating thickness on the microstructure and mechanical properties of Al-Si alloy (LM6) produced using the investment casting technique was investigated. A ceramic mold with four different layers (3, 4, 5 and 6 layers) of thickness was prepared using aluminum oxide (Al2O3) together with slurry and stucco. The result shows that the highest tensile strength value obtained from the three layers of coating is 161.67 MPa. Furthermore, an additional layer of coating thickness does not affect the structure of the aluminum alloy (LM6). The microstructure pattern shows an eutectic silicon formation on the wall of the mold at a higher intensity compared to the center. The results also showed that coating thickness has a significant effect on the microstructure located between the wall and the center. Heat transfer of the thinner coating is improved compared to the thicker coating. Indirectly, the formation of high density needle silicon on the wall gives better strength to the alloy.